Gambaran Kejadian Partus Prematurus Imminens - Ni Kadek Sudiani; Ni Ketut Somoyani; I Nyoman Wirata (ProHealth Journal, 2026)
Partus Prematurus Imminens (PPI) is a threat to pregnancy caused by signs of labor in a gestational age of less than 37 weeks. PPI that is not immediately treated will result in premature labor. The purpose of this study was to determine the incidence of Partus Prematurus Imminens at the Wangaya Regional General Hospital, Denpasar City. This type of study was descriptive with a cross sectional approach. The study was conducted on March 3 to May 14, 2025. The population of this study were all pregnant women with Partus Prematurus Imminens in 2020 - 2024 at the Wangaya Regional General Hospital, Denpasar City, the total population were 286 people. The sampling technique used was purposive sampling. The sample size was 167 subjects. The type of data was secondary data. Data was collected with a check list sheet. Data analysis used univariate analysis. The results of this study, the incidence of PPI at Wangaya Regional General Hospital, Denpasar City was 83.8% at the age of 20-35 years, 83.2% in high school education, 50.9% in working mothers, 50.3% in nulliparous, 18.6% in mothers with a history of abortion, 20.9% in mothers suspected of UTI, 15% in mothers with anemia, 50.3% of antenatal visits were inappropriate and never ANC, 89.8% of conservative care was successful. The conclusion of this study, the incidence of PPI in Wangaya Regional General Hospital, Denpasar City is highest in the age of 20-35 years, high school education, working mothers, nulliparous, and ANC is not appropriate or has never been ANC. The study suggest that pregnant women have ANC according to standards, limit heavy activities, and and get enough rest. In future study, it is recommended to use primary data.